ANALISIS METODE MUROJAAH AL-QUR’AN UNTUK MENINGKATKAN KUALITAS HAFALAN DI PONDOK PESANTREN TAHFIDZUL QUR’AN ASY SYADZILI EMPAT MALANG - Holiza Yanti (Program Studi Pendidikan Agama Islam STIT al Urwatul Wutsqo Bulurejo Jombang, 2026)
This study aims to examine the stages of implementing the murojaah method of the Qur’an, its effectiveness in maintaining the quality of students’ memorization to achieve the level of mutqin, as well as the supporting and inhibiting factors in its implementation at Pondok Pesantren Tahfidzul Qur’an Asy Syadzili 4 Malang. This research employs a descriptive qualitative approach with data collection techniques including observation, interviews, and documentation. The results indicate that the murojaah method at this pesantren is implemented in a structured and systematic manner through memorization tests, tashih, and tasmi’ programs. The implementation of this method has proven effective in maintaining and improving the quality of students’ memorization, as evidenced by more fluent, strong, and stable memorization that reaches the mutqin level. Furthermore, the murojaah method enhances students’ discipline, sense of responsibility, and mental readiness in presenting their memorization of the Qur’an, enabling them to confidently participate in tasmi’ of 15 and 30 juz. Supporting factors for the success of the murojaah method include sincere intention, motivation, interest, intelligence, support from parents and teachers, a conducive environment, and adequate facilities. Meanwhile, inhibiting factors include decreased motivation, lack of concentration, and differences in students’ abilities. Thus, the murojaah method implemented at Pondok Pesantren Tahfidzul Qur’an Asy Syadzili 4 Malang is proven to be effective in maintaining the quality of Qur’anic memorization and in forming mutqin students with Qur’anic character.